Pengaruh Penerapan Model Pembelajaran Berpikir Induktif Menggunakan Media Pembelajaran Berbasis HTML 5 Package (H5p) Terhadap Motivasi Belajar dan Tanggung Jawab Belajar Siswa - Sudarmawanto Sudarmawanto (Universitas 45 Surabaya, 2025)
This study aims to analyze the effect of implementing an inductive thinking learning model using html 5 package (H5P)-based learning media on students' learning motivation and learning responsibility. The research method uses a quantitative approach. The research sample was 29 students of class XI TKJ 1 SMK PGRI 13 Surabaya. The data collection technique used a questionnaire and data analysis techniques with SPSS-assisted linear regression. The results of the study prove that the inductive thinking learning model using html 5 package (H5P)-based learning media has a significant positive effect on students' learning motivation and learning responsibility.